Floral boilogy of large cardamom (Amomum subulatum) - Kishore, Kundan; Kalita, H; Rinchen, D; Pandey, Brijesh (The Indian Journal of Agricultural Sciences, 2012)
A study on floral phenology, floral visitors, foraging nature of floral visitors, nectar production, pollination efficiency and stigma receptivity of large cadamom (Amomum subulatum Roxb.) of the family Zingiberaceae conducted during 2009–10. Anthesis in large cardamom took place in the early morning (around 5:30 am) and flowers offer plenty of anthers and moderate amount of nectar to floral visitors. There were four floral visitors; bumble bee (Apis braviceps Smith), honey bee (Apis cerena), fruit fly (Bactocera sp.) and moth (Udaspes folus), and among them A. braviceps was found to be the major pollinator due to its high pollination efficiency attributed to its big body size and foraging habit, while A. cerena acts as a pollen robber. Each flower receives 45.92 visits of bumble bee with the foraging time of 118.93 seconds in a day. Pollination efficiency of bumble bee was as high as 100% while honey bee could pollinate only 8.41% of flower. Bumble bee delivers pollens in the receptive cup pf stigma, in contrary honey on the non-receptive hairs surrounding stigma cup. Nectar secretion begins at 9 hr on the day anthesis and reaches to its peak at 14 hr, followed by reduction in nectar production. A temperature range of 25–28°C and air humidity of 50–60% favoured high nectar production. Increase in 0.77 unit of temperature and decrease in 2.04 unit of air humidity resulted in 1 unit increase in nectar content. The visitation frequency and foraging time of bumble bee were not correlated with the nectar production. Bumble bee and honey bee had almost equal pollen load, but pollen carrying mechanism was quite different as honey bee carries pollen in pollen basket and bumble bee on its head and thorax. Stigma became receptive 12 hr before anthesis (protogynous) and remains receptive even after 15 hr of flower senescence. The best time of pollination was between 6 and 9 hr on the day of anthesis.